2013
DOI: 10.1002/asi.22963
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of green open access

Abstract: Open Access (OA) is the free unrestricted access to electronic versions of scholarly publications. For peer reviewed journal articles there are two main routes to OA, publishing in OA journals (gold OA) or archiving of article copies or manuscripts at other web locations (green OA). This study focuses on summarizing and extending upon current knowledge about green OA. A synthesis of previous studies indicates that the green OA coverage of all published journal articles is approximately 12 %, with substantial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
1
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(168 citation statements)
references
References 38 publications
7
150
1
10
Order By: Relevance
“…Jubb et al, have recently produced a report highlighting the rapid rise of green and gold OA uptake in the UK-rises which can be reasonably attributed, at least in part, to strong OA policy mandates [8]. However, others argue that these mandates alone cannot transform the scholarly publishing environment [33,34], emphasising that major barriers remain in author behaviours and academic cultures.…”
Section: Rise Of Open Access and Mandatesmentioning
confidence: 99%
“…Jubb et al, have recently produced a report highlighting the rapid rise of green and gold OA uptake in the UK-rises which can be reasonably attributed, at least in part, to strong OA policy mandates [8]. However, others argue that these mandates alone cannot transform the scholarly publishing environment [33,34], emphasising that major barriers remain in author behaviours and academic cultures.…”
Section: Rise Of Open Access and Mandatesmentioning
confidence: 99%
“…Harnad (2015), one of the earliest writers on green OA, provides a framework for instituting effective institutional and funder OA mandates that would support the growth and ultimate achievement of universal green OA. Björk, Laakso, Welling, and Paetau (2013) present a background on the history of green OA and related studies, including research on author attitudes and behaviors regarding self-archiving and preference for different article versions. Further, they suggest that green OA coverage of all published journals (as of 2013) hovers at 12%, with substantial disciplinary differences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study of self-archiving at Carnegie Mellon University found that, of the articles that faculty made publicly available online, only half were posted in accordance with the publishers' policies (Covey, 2009). Bo-Christer Björk, Mikael Laakso, Patrik Welling, and Patrik Paetau (2014) found that many authors upload publisher-typeset versions of their articles to the Web even though very few publishers allow authors to distribute this version. In order to comply with publisher policies on the distribution of articles, institutional repositories such as DASH need to reliably determine the version of articles submitted for distribution.…”
Section: Introductionmentioning
confidence: 99%